Nonlinear FVDs for Seismic Resilience of Irregular RC Buildings - Gupta, Bed Prakash (Everest Advances in Science and Technology, 2025)
Passive energy dissipation systems, particularly fluid viscous dampers (FVDs), offer a promising alternative by enhancing damping ratios without significantly altering structural stiffness. Despite their global success, FVDs remain underutilized in Nepal due to limited studies and the absence of specific provisions in the Nepal Building Code (NBC 105:2020). This study addresses this gap by evaluating the efficacy of FVDs in enhancing the seismic performance of a 10-storey representative building with setback, exhibiting vertical irregularities using performance-based design principles in SAP2000 v20. Nonlinear behavior is modeled using a lumped plasticity approach, with user-defined moments M3 hinges for beam and auto hinges PM2M3 for columns as per ASCE 41-13. Pushover analysis determines the capacity curve, which is matched with NBC 105:2020 elastic spectrum to identify performance point and ensure compliance with the Immediate Occupancy (IO) performance level. FVDs are modeled as two-noded nonlinear link elements and strategically placed at stories with maximum inter-storey drift. Non-linear time history analysis (NLTHA), employing the direct integration and spectrum-compatible ground motion records for Type D soil (DBE, 10% probability of exceedance in 50 years), evaluates maximum storey displacements and hinge states. Comparative results between damped and undamped models are analyzed to quantify performance improvements. The results demonstrate that FVDs significantly reduce displacements and maintain hinge state within the IO performance level, offering practical and effective strategy for enhancing seismic resilience.